EROTIKA DAN PORNOGRAFI DI MEDIA - Wiryanto, Wiryanto (Universitas Prof. Dr. Moestopo (Beragama), 2006)
Pornography is anything that is created to cause sexual excitement or arousal. Most of us think of : erotic imagery that is considered obscene and Offensive. Pornographi (From GreekÂ ÏOpvoypaÏia pornographia - literally writing about or human sexual behavior with the goal of sexual arousal, similar to, but (axxording to some) distinct from. Erotica it also âprostituteâ and âwritten materialâ. Which representations of the human body or human sexual behavior with the goal of sexual orusal, similar to, but human sexual behavior with the goal of sexual arouseal, similar to. But distrinct from, erotica though the two terms are often used interchangeably.Pornographi may use any of avariety of media â written and spoken text. Photos, sculpture, drawings, moving images (including animations), and sounds such as heavy breathing and sexually related sounds. Pornogaphic films combine moving images, spoken erotic text and/or other erotic sounds. While magazines often combine photos and written text. Novels and short stories provide written text, sometimes with illustrations, A live performance may also be called pornographic.Opposition to pornography generally, though not exclusively, comes from several sources : law, religion like mazhab wahabi and feminism there is no right to distribute obscene materials, child pornography is illegal. The determinatios of what is obscene is up to a jury in a trial. Most religious groups view pornography as immoral and the production and use of pornography contributes to immoral behavior in society. Feminist critics of pornography. They believe that most pornography eroticizes the dominations, humiliation and coercion of women, reinforces the domination, humilations and coercion of women, reinforces sexual and cultural attitudes that are complicit rape and sexual harassment, and contributes to the male centeredÂ to the male centered objectification of women.